Forecasting investment and consumption behavior of economic agents through dynamic computable general equilibrium model - Irfan Ahmed; Claudio Socci; Francesca Severini; Qaiser Rafique Yasser; Rosita Pretaroli (Financial Innovation, 2018)
Much research has been devoted to examination of the financial easing policy of the European Central Bank (ECB). However, this study is one of the first to use a dynamic micro-founded model to investigate empirically the impact of the ECB's Quantitative Easing (QE) policy on consumption and investment by economic agents in Italy (households, government, firms, and the rest of the world). For this purpose, we constructed a Financial Social Accounting Matrix (FSAM) for the Italian economy for the year 2009 to calibrate a dynamic computable general equilibrium model (DCGE). This model allowed us to evaluate the direct and indirect impact of money flow on the behavior of consumption and investment. The findings of the study confirmed the positive impact of the ECB's monetary policy on the level of investment and consumption.
Keywords: C63; E17; E52; D57; 650; European Central Bank; Quantitative easing; Monetary policy; Investment behavior; Social accounting matrix; Dynamic CGE analysis